Design Process: A Digital Dashboard for Boats - Kurki, Eden (My University, 2025)
This thesis explores the principles of usability and user interface design within the context of maritime technology, focusing on the design process of a digital dashboard for boats. In this context, a digital dashboard refers primarily to an interactive digital touchscreen that displays information. By applying user-centered design (UCD) and conducting a survey to gather user preferences, this study highlights the importance of integrating user feedback to enhance usability and user satisfaction. The findings show that iterative design and user research contributed to the creation of a functional and aesthetically pleasing digital dashboard. The final design incorporated features such as a map integration, additional pages, multiple engines support, and new color schemes. Additionally, future studies could explore further improvements in other design areas or conduct a post-launch survey to ensure user needs are met.
Keywords: Usability, digital dashboards, digital screens, UI, design, maritime, navigation systems